2022
DOI: 10.5194/aab-65-37-2022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of porcine milk microRNA expression in milk exosomes versus whole swine milk and prediction of target genes

Abstract: Abstract. Milk exosomal microRNAs (miRNAs) are important for postnatal growth and immune system maturation in newborn mammals. The functional hypothesis of milk exosomal miRNAs and their potential bioavailability in milk to newborn mammals were investigated. Briefly, 37 exosomal miRNAs were upregulated compared to miRNAs found outside the exosomes. Among these miRNAs, ssc-miR-193a-3p expression was upregulated 1467.35 times, while ssc-miR-423-5p, ssc-miR-551a, ssc-miR-138, ssc-miR-1 and ssc-miR-124a were highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Milk and its signaling components have been identified as a unique signal transduction system activating mTORC1 [ 70 ], which is the central kinase of metabolism orchestrating growth signals and nutrient availability for cell growth and anabolism [ 71 , 72 , 73 , 74 , 75 , 76 ]. Importantly, target gene prediction of human, bovine, and porcine MEX miRs mainly concentrate on PI3K-AKT-mTORC1 pathway activation [ 28 , 77 , 78 , 79 ].…”
Section: Postnatal Mex Mir Signaling Promotes Pancreatic β Cell Proli...mentioning
confidence: 99%
“…Milk and its signaling components have been identified as a unique signal transduction system activating mTORC1 [ 70 ], which is the central kinase of metabolism orchestrating growth signals and nutrient availability for cell growth and anabolism [ 71 , 72 , 73 , 74 , 75 , 76 ]. Importantly, target gene prediction of human, bovine, and porcine MEX miRs mainly concentrate on PI3K-AKT-mTORC1 pathway activation [ 28 , 77 , 78 , 79 ].…”
Section: Postnatal Mex Mir Signaling Promotes Pancreatic β Cell Proli...mentioning
confidence: 99%
“…Chen et al [ 31 ] sequenced pig milk exosomes and found that they contained 176 known and 315 novel mature miRNAs. Liu et al [ 32 ] detected 208 pre-miRNAs and 200 mature miRNAs in pig milk exosomes. However, it is not known whether the characteristics of milk exosomes and miRNA expression are related to the breed and milk type.…”
Section: Discussionmentioning
confidence: 99%
“…To identify exosomal miRNAs in the colostrum and mature milk of Bamei and Landrace pigs, 12 small RNA libraries were constructed and sequenced, namely, the BMo (n = 3), BMc (n = 3), LWo (n = 3), and LWc (n = 3) groups, respectively (Section 4.2). In total, 108,497,788 (valid reads 25,444,101), 112,049,590 (valid reads 32,228,194), 108,283,662 (valid reads 14,426,719), and 104,916,517 (valid reads 31,565,425) total reads were obtained in the BMo, BMc, LWo, and LWc groups, respectively (Table 1). We performed a length distribution statistical analysis on the total number of filtered miRNA data.…”
Section: Quality Control Of Sequencing Datamentioning
confidence: 99%
“…MEX miR-21 and miR-148a target phosphatase and tensin homolog (PTEN) and promote PI3K-AKT-mTORC1 signaling (77,105). Indeed, target gene prediction of human, bovine and porcine MEX miRs mainly concentrate on the PI3K-AKT-mTORC1 pathway (30,73,106). Increased trophoblast mTORC1 activity determines placental-fetal transfer of amino acids and glucose promoting fetal growth and birth weight (107)(108)(109)(110)(111)(112).…”
Section: Bovine Mex Mir Exposure During Pregnancymentioning
confidence: 99%
“…Functional analysis for the most abundant mRNAs of bovine MEX showed epigenetic functions such as histone modification, telomere maintenance, and chromatin remodeling (79). Liu et al (106) identified methyl CpG binding protein 2 (MeCP2) as target gene of the most abundant miRs of porcine MEX. MeCP2 induces a repressive state of chromatin by recruiting histone deacetylases (HDACs), methyltransferases and other chromatin-silencing factors, which increase chromatin condensation and prevent transcription (183)(184)(185)(186).…”
Section: Transcriptional Activity and Chromatin Remodelingmentioning
confidence: 99%